Neo-Latin Drama in Early Modern Europe and Beyond - Bloemendal, Jan, (Brill Research Perspectives in Humanities and Social Sciences., 2026)
Neo-Latin Drama in Early Modern Europe and Beyond addresses the development and transnational circulation of Neo-Latin drama, as well as its interaction with vernacular drama and the role of classical reception. It also suggests ways to further explore the corpus using digital tools. By providing an overview of the history of Neo-Latin drama in its secular, Protestant, or Roman Catholic (especially Jesuit) forms, it offers non-specialists an accessible introduction to this fascinating body of texts, which is central to early modern intellectual culture.